Gramsci and Social Work: philology as a method of study - Gomes, Renato de Brito (Argumentum, 2025)
This article presents the methodologies developed since the 1970s for the reading and study of the Cadernos do cárcere. The appropriation of the Cadernos by Social Service is investigated and an interpretive hypothesis is made associated with two cycles of Gramscian research in which the outcome depends on the sources of access to the work. Finally, a reading of Gramsci is suggested that seeks the “rhythm of thought” through a chronological reading of the entirety and fragmentary nature of the notes, understanding their nuances, developments, and reformulations, and how the Brazilian “critical-thematic” edition can offer endurance in this regard. It concludes that the eventual incorporation by social workers of updated reading tools and even new interpretations will, once again, generate important research.